Answer:
Explanation:
Before finding the value of x which is the base in the right triangle, we must have to find the perpendicular in the left angle triangle.
So, In the left triangle,
→ (Base)² + (Perpendicular)² = (Hypotenuse)²
→ (10)² + (Perpendicular)² = (16)²
→ (Perpendicular)² = (16)² – (10)²
→ (Perpendicular)² = 256 – 100
→ (Perpendicular)² = 156
→ Perpendicular = √(156)
→ Perpendicular = 12.4
Now, In the right triangle, we have :
→ (Base)² + (Perpendicular)² = (Hypotenuse)²
→ (x)² + (12.4)² = (28)²
→ (x)² = (28)² – (12.4)²
→ (x)² = 784 – 153.7
→ (x)² = 630.3
→ x = √(630.3)
→ x = 25.1
Therefore,